Spontaneous excitatory transmission enhancement produced by linalool and its isomer geraniol in rat spinal substantia gelatinosa neurons - involvement of transient receptor potential channels - Chong Wang; Tsugumi Fujita; Hiroki Yasuda; Eiichi Kumamoto (Elsevier, 2022)
Background: Many of plant-derived compounds inhibiting nerve conduction enhance glutamatergic spontaneous excitatory transmission by activating transient receptor potential (TRP) channels in spinal substantia gelatinosa (SG) neurons that play a crucial role in regulating nociceptive transmission. Although (±)-linalool and its isomer geraniol having antinociceptive effects inhibit nerve conduction, it has not been examined yet how they affect excitatory transmission in SG neurons. We examined the effects of the compounds on action potential-independent spontaneous excitatory transmission with a focus on an involvement of TRP channels. Methods: The whole-cell patch-clamp technique was applied to SG neurons in adult rat spinal cord slices. Results: (±)-Linalool increased the frequency of spontaneous excitatory postsynaptic current (sEPSC) with a small increase in its amplitude. The (±)-linalool activity was sensitive to TRP vanilloid-1 (TRPV1) antagonist capsazepine and TRP ankyrin-1 (TRPA1) antagonist HC-030,031 while resistant to BCTC that is antagonist for cloned TRPV1 and TRP melastatin-8 (TRPM8) channels and for TRPM8 channels in the SG, indicating TRPV1 and TRPA1 activation. In 73% of the neurons tested, (±)-linalool produced an outward current at -70 mV. In SG neurons sensitive to (±)-linalool, geraniol produced a quantitatively similar effect to (±)-linalool. Geraniol-induced sEPSC frequency increase was sensitive to BCTC but resistant to capsazepine and HC-030,031, indicating TRPM8 activation. Outward currents produced by (±)-linalool and geraniol were unaffected by all of the TRP antagonists. Conclusion: In SG neurons, (±)-linalool and geraniol presynaptically enhanced spontaneous excitatory transmission by activating different types of TRP channel while hyperpolarizing membranes in a manner independent of TRP channels. Such a TRP channel modulation and hyperpolarization could contribute to the antinociceptive effects of (±)-linalool and geraniol.